ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENGUMUMAN PEMBOIKOTAN PRODUK ISRAEL - Muchran, Muchriana; Marsyida, Elvi Amira; Ikhtiar Arta, Cut Putri; Simpajo, Nurul Mumtazah; Awal, Arif (IJMA (Indonesian Journal of Management and Accounting), 2024)
This study aims to examine the difference in the financial performance of companies before and after the announcement of the boycott of Israeli products. This study uses a type of quantitative research with a descriptive approach. Quantitative research was chosen because it aims to test the research hypothesis that has been proposed. Descriptive approach is a method based on the philosophy of positivism, used to examine a particular population or sample. The analysis methods used are descriptive analysis tests, hypothesis tests with the Paired Sample t-test. With a research sample, namely companies affected by the boycott listed on the Indonesia Stock Exchange (IDX). Financial performance will be analyzed through three financial ratios, namely the liquidity ratio measured by the current ratio, the leverage ratio measured by the debt to equity ratio, and the profitability ratio measured by return to assets as well as the financial statements observed in the 3rd and 4th quarters. The results of this study show that the Current Ratio (CR) shows a significant difference between before and after the announcement of the boycott of israil products. Debt to Equity Ratio (DER) and Return To Asset (ROA) did not show a significant difference between before and after the announcement of the boycott of Israeli products.